Improving the Energy Performance Certificate recommendations' accuracy for residential building through simple measurements of key inputs. Issue 3 (September 2019) - Gonzalez-Caceres, A; Arvid Vik, T; Granheim, P; fælth, J P; Berg, L
Abstract: The Energy Performance Certificate (EPC) allows building users to be informed and aware of the quality of the buildings in terms of energy needs. Additionally, the EPC includes a future for existing buildings, which is the incorporation of a Recommendation list of Measures (RLMs) to improve their energy performance in a cost-effective way. Which have risen the question if this tool can provide trustful Cost-effective recommendations due despite the uses of standardized inputs. This study focuses on estimating the impact of using measure ventilation rate, heating set point and airtightness on the profitability of the recommendations. The study is based on common dwelling in Norway, comparing results obtained with a Building Performance Simulation Software, following the Norwegian standard for energy certification and with the uses of measured ventilation rate, airtightness and real heating set points. The results show that the performance gap can be reduced significantly just by adopting these inputs, increasing the confidence on the RLMs and reducing the uncertainty of the investment.